Translation and validation of modified checklist for autism in toddlers-revised version in Tamil (T-MCHAT-R) - Perumal Santhanam Divya; Jasmine Lydia Selvaraj; Priscilla P; Sai Sreya R. (Journal of Child Language Acquisition and Development, 2020)
The Modified Checklist for autism in toddlers - revised (MCHAT-R) (Robin et al 2001) is a simple questionnaire for parents which improves discrimination between autism and other developmental disorders. This screening tool is currently available in more than 20 languages of the World. The aim of the current study is adaptation and validation of the Modified Checklist for Autism in Toddlers (M-CHAT-R) in the Tamil language. A total of 450 children from both sexes between 16 to 30 months of age were taken, and those who have any comorbid serve chronic diseases were excluded. For the reliability of T-MCHAT-R, statistical analysis was done by using SPSS version 20.0. The Cronbach's Alpha test found out that the T- MCHAT- R has an alpha score of 0.894 on a standardized item, which is categorized as excellent reliability. Pearson's two-tailed correlation was performed to compare T-MCHAT-R scores with ISAA scores which reveal a positive correlation (r=0.01). The ‘p’ value for T-MCHAT-R and ISAA for both the normal and abnormal groups was >0.001 indicating that the results are highly significant. Our results yielded reliability and validity estimates similar to the values of the original M-CHAT validity study (Robins et al. 2001). We have shown that the Tamil version of M-CHAT-R has divergent Validity. The Tamil version of M-CHAT-R has shown satisfactory reliability. Hence it is an effective tool for screening for ASD in medium and high-risk children and should be regarded as the first official Tamil version of the M-CHAT-R to be applied in Tamil Nadu.